Gut microbiota and osteoarthritis: epidemiology, mechanistic analysis, and new horizons for pharmacological interventions - Sun, Nianyi; Zhao, Yinuo; Zhang, Anren; He, Yu (Frontiers in Cellular and Infection Microbiology, 2025)
Emerging evidence suggests that gut microbiota dysbiosis is associated with the onset and progression of osteoarthritis (OA). While OA was traditionally considered a localized degenerative joint condition, it is now increasingly viewed as a systemic disorder involving low-grade inflammation and metabolic imbalance. This review synthesizes current findings on the gut–joint axis and presents a structured overview of how alterations in microbial communities may relate to phenotypic variability in OA. Observational studies have identified correlations between gut dysbiosis and factors such as obesity and hyperuricemia, which are themselves linked to increased intestinal permeability, elevated circulating lipopolysaccharide levels, and reduced production of short-chain fatty acids. These features may contribute to immune dysregulation and tissue degeneration, although definitive causal mechanisms remain unconfirmed. Some reports have also detected microbial DNA in joint tissues, raising the possibility of microbial translocation and its potential role in local inflammatory processes. In light of these associations, we review several microbiota-directed interventions, including probiotics, dietary supplements, Traditional Chinese Medicine, and biomaterial-based approaches. Although preliminary studies suggest these strategies may influence systemic inflammation and joint health, most evidence is derived from preclinical models or small-scale clinical trials. Causality has not yet been firmly established, and further validation in larger, well-controlled studies is needed. By integrating current mechanistic insights with emerging therapeutic directions, this review highlights the potential relevance of the gut–joint connection in OA and underscores the importance of continued research toward microbiota-informed, individualized approaches to disease understanding and management.